THE AFFECT OF TEACHERS TEACHING SKILLS AND LEARNING FACILITIES ON STUDENTS LEARNING MOTIVATION - Marsofiyati; Christian Wiradendi Wolor; Muthi Rahmawati Faza (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of teacher teaching skills and learning facilities on student motivation at SMK Negeri 51 Jakarta. This research was conducted for 9 months starting from January 2022 to September 2022. The method used in this study is a survey method. The respondent selection technique used purposive sampling so that a sample of 150 respondents was obtained from students of SMK Negeri 51 Jakarta from all skill competencies. Data was collected through distributing questionnaires using a Likert scale. Based on the results of the research conducted, it was found that Teacher's Teaching Skills had a positive and significant effect on Learning Motivation. Learning Facilities have a positive and significant effect on Learning Motivation. In accordance with the research hypothesis